2022
DOI: 10.3390/genes13081430
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Genomic Prediction Approach for Predicting Buffalo Milk Traits by Incorporating Related Cattle QTLs

Abstract: Background: The 90K Axiom Buffalo SNP Array is expected to improve and speed up various genomic analyses for the buffalo (Bubalus bubalis). Genomic prediction is an effective approach in animal breeding to improve selection and reduce costs. As buffalo genome research is lagging behind that of the cow and production records are also limited, genomic prediction performance will be relatively poor. To improve the genomic prediction in buffalo, we introduced a new approach (pGBLUP) for genomic prediction of six b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Earlier studies (e.g., Esfandyari et al [3], Lee et al [4], and Zha et al [5]) have suggested that meat color traits in pigs demonstrate low to moderate heritability, indicating the significant contribution of genetic factors to the variation in these traits. Therefore, through a comprehensive analysis of the genetic mechanisms underlying meat color traits and the identification of relevant candidate sites and genes, which can in turn enhance the efficiency of marker-assisted selection or genomic selection, valuable insights for the genetic improvement of the traits can be provided [6][7][8][9]. According to the release 48 version of the animal quantitative trait loci (QTLs) database [10], a total of 18,265 QTLs or associations for porcine meat quality and carcass traits have been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies (e.g., Esfandyari et al [3], Lee et al [4], and Zha et al [5]) have suggested that meat color traits in pigs demonstrate low to moderate heritability, indicating the significant contribution of genetic factors to the variation in these traits. Therefore, through a comprehensive analysis of the genetic mechanisms underlying meat color traits and the identification of relevant candidate sites and genes, which can in turn enhance the efficiency of marker-assisted selection or genomic selection, valuable insights for the genetic improvement of the traits can be provided [6][7][8][9]. According to the release 48 version of the animal quantitative trait loci (QTLs) database [10], a total of 18,265 QTLs or associations for porcine meat quality and carcass traits have been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of genomic selection in buffalo breeding (Bubalus bubalis) has been considered to improve the economic situation of small-scale producers in the world, as well as the unique characteristics of its milk. However, it has also been reported that buffalo genome research is lagging behind that of the cow, and production records are also limited, as the genomic prediction performance will be relatively poor (Hao et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The results of one study showed that genomic selection can reduce the generation interval in the path of male-to-male selection from 9.5 years to 3. and Bayesian alphabet methods (Hao et al 2022). In the study of genomic selection with different methods in buffaloes of the Philippine, it has been reported that genomic methods (GBLUP and ssGBLUP) provide more accurate predictions compared to pBLUP (Herrera et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation